2022
DOI: 10.1186/s13089-022-00262-w
|View full text |Cite
|
Sign up to set email alerts
|

The association of ultrasound assessment of gallbladder wall thickness with dengue fever severity

Abstract: Objectives To evaluate the association between ultrasound assessment of gallbladder wall thickness (GBWT) among severe dengue patients and dengue patients with warning signs to their clinical outcomes. Methods A prospective, cross-sectional study involving adult dengue patients presented to our emergency department between March until September 2018. The patients were classified based on WHO classification. A gallbladder wall scan was performed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was reported that the edema of the gall bladder is associated with the dengue hemorrhagic fever, so every dengue patient should be screened for it (Adil et al 2020). The sensitivity and specificity of the thickness of the gall bladder in assessing the admission to the intensive care unit or general ward were 100% and 62.1% (Ibrahim et al 2022). The thickening of gallbladder, which is detected radiologically, can predict the disease progression in ambulatory patients in the early stages of dengue (Gleeson et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the edema of the gall bladder is associated with the dengue hemorrhagic fever, so every dengue patient should be screened for it (Adil et al 2020). The sensitivity and specificity of the thickness of the gall bladder in assessing the admission to the intensive care unit or general ward were 100% and 62.1% (Ibrahim et al 2022). The thickening of gallbladder, which is detected radiologically, can predict the disease progression in ambulatory patients in the early stages of dengue (Gleeson et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…13 Diante da falta de recomendações específicas do GRADE para definir "evidência indireta" ou distingui-la de "evidência direta", optamos por seguir a definição da Society for Desses 14 estudos incluídos, somente 7 (50%) especificamente mencionaram que pacientes da emergência haviam sido incluídos. [26][27][28]31,32,34,35 A população desses estudos foi bastante heterogênea no que se refere aos critérios de inclusão, desde pacientes com dengue confirmada sem sinais de alarme até pacientes exclusivamente internados classificados como dengue hemorrágica na classificação antiga da OMS. Essa heterogeneidade da população precluiu qualquer tipo de meta-análise ou agrupamento dos dados.…”
Section: Uso De Evidências Indiretasunclassified
“…A maioria dos estudos usou o ponto de corte de 3 milímetros para definir a parede como espessada. [23][24][25]27,29 Um estudo utilizou a definição de colecistite acalculosa aguda definida por Huffman, 40 considerando ponto de corte maior que 3,5 -4 mm. 26 Nenhum estudo avaliou o método "eyeballing", isto é, avaliação da espessura da parede sem quantificação numérica da mesma.…”
Section: Uso De Evidências Indiretasunclassified